1993
DOI: 10.1159/000129306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distal Gastrectomy on Gut Hormone Release following Vagal Stimulation in Dogs

Abstract: The effect of distal gastrectomy on gut hormone release was investigated by electrical stimulation of the posterior truncal vagus in dogs. Peripheral and portal plasma gastrin release was significantly inhibited, but peripheral and portal somatostatin release was unchanged. Peripheral and portal pancreatic polypeptide (PP) release was significantly inhibited. Our results suggest that the following factors might be some of the reasons why the secretion of PP was inhibited after distal gastrectomy: (l)transectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…This procedures takes advantage of intestinal peristalsis and the tolerance of the jejunum to acidic gastric juice and alkaline digestive juice. Kameyama et al first reported that the interposition of a jejunal pouch could preserve storage capacity in the remnant stomach (9). Katai et al reported that the incidence of reflux symptoms after jejunal interposition was 5.6%, and that of reflux esophagitis on endoscopy was 1.7%, which significantly improved the patients' postoperative quality Jejunal interposition: a segment of jejunum is inserted between the esophagus and the remnant stomach to construct an antireflux barrier.…”
Section: Jejunal Interpositionmentioning
confidence: 99%
“…This procedures takes advantage of intestinal peristalsis and the tolerance of the jejunum to acidic gastric juice and alkaline digestive juice. Kameyama et al first reported that the interposition of a jejunal pouch could preserve storage capacity in the remnant stomach (9). Katai et al reported that the incidence of reflux symptoms after jejunal interposition was 5.6%, and that of reflux esophagitis on endoscopy was 1.7%, which significantly improved the patients' postoperative quality Jejunal interposition: a segment of jejunum is inserted between the esophagus and the remnant stomach to construct an antireflux barrier.…”
Section: Jejunal Interpositionmentioning
confidence: 99%
“…Beim Menschen bewirkt Scheinfu È tterung einen prompten Anstieg der PP-Sekretion, die vagal stimuliert wird [37,28]. Nach Gastrektomie ist die Gesamtsekretion von PP deutlich reduziert, was mit den fehlenden vagalen Reizen nach Gastrektomie erkla Èrt werden kann [1,9,39]. In der klinischen Studie von Friess et al [9] ist der PP-Basalwert nach Gastrektomie um 61% und die PP-Gesamtsekretion um 42% niedriger.…”
Section: Pp Wird Von Den In Den Langerhansschen Inseln Und Im Exokrinunclassified